Validating the Turkish Version of the Self-Directed Online Learning Scale (SDOLS-T): An Empirical Psychometric Study - Karabatak, Songul; Alanoglu, Muslim; Yang, Hongwei; Su, Jian (Springer, 2025)
The objective of this study is to assess students' perceptions of self-directed learning (SDL) skills in online learning using the Turkish version of the Self-Directed Online Learning Scale (SDOLS-T). To achieve this objective, the original SDOLS in English was translated into Turkish using the back-translation method. Subsequently, two separate data collection studies were carried out with a sample of undergraduate students at a university in T & uuml;rkiye at two different time points (T1 and T2). At T1, data was collected using only the SDOLS-T, while at T2, both the SDOLS-T and the Turkish version of the Online Learning Self-Efficacy Scale (OLSES-T) were administered to the students. The data collected at T1 was analyzed to examine the validity of the original factor structure in the Turkish culture. Moreover, measurement invariance across gender and class level categories was tested. Reliability evidence was also assessed through internal consistency and composite reliability tests. At T2, data was collected for both the SDOLS-T and the OLSES-T, and the convergent validity was evaluated using this data. Furthermore, test-retest reliability was measured by calculating the correlation between the means of T1 and T2 to ascertain the stability of the SDOLS-T. The results obtained provide support for the psychometric adequacy of the SDOLS-T and its potential utility in online teaching and learning practices, policy-making, and research in T & uuml;rkiye. Additionally, the implications of this study suggest that the SDOLS is a scale that can effectively measure self-directed learning skills, which are crucial for students' learning, across diverse cultures and facilitate their assessment.
Keywords: Self-directed learning; Online learning; Self-directed online learning; Measurement invariance; Confirmatory factor analysis